Melihat Indonesia dari Jendela Papua: Kebinekaan dalam Rajutan Budaya Melanesia - Kadir, Akhmad (JSW (Jurnal Sosiologi Walisongo), 2017)
This article reveals the dynamics of local communities in Papua in accommodating differences between them. Those different ethnic and cultural communities, are able to build social relations through cultural mechanisms. Using the ethnographic approach this article reveals that Papuan people have a strong cultural capital to relate existing differences. Through communal culture, exchange relation in the form of enjoying eating together, religion of relatives, and the culture of one stone stove made of three stone, as well as inter-clans marriage become the mechanism that becomes elements of social glue between the community members. Although tribal conflicts often occur, traditional communities have a way of handling conflict through cultural mechanisms, such as "eating together", "burning stones" and accompanied by slaughter of sacrificial animals.